(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The concept of a spiritually perfect person is a comprehensive, multifaceted concept. A spiritually perfect person is in harmony with the concept of a perfect person. At this time, the concept of a spiritually perfect person is also associated with the concept of a healthy generation. Although these concepts are used separately in the scientific literature, in fact they all cover all aspects of human morality and morality, all positive feelings formed in them, starting from their attitude to people, society and homeland and ending with their attitude to family, parents, etc.